English: SAD KERTIH KEARIFAN LOKAL BALI DALAM PERSPEKTIF PENGENDALIAN LINGKUNGAN HIDUP - Anak Agung Putu Wiwik Sugiantari; Ni Luh Gede Yogi Arthani; Agustina Ni Made Ayu Darma Pratiwi; Ni Kadek Yuliniantari; Ni Nyoman Manik Gita Asrita (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study focused on the role of Sad Kertih, a policy concept based on Balinese local wisdom, from the perspective of environmental control. Bali, with its rich culture and traditions, has developed various environmental management practices rooted in local values, one of which is through the Sad Kertih system. This system combines social, cultural, and ecological aspects to maintain environmental sustainability and the sustainability of Balinese people's lives. The purpose of this study is to explore how Sad Kertih can contribute to environmental control and preservation, both locally and globally. With a local wisdom approach, this system not only prioritizes respect for nature but also empowers communities to play an active role in sustainable natural resource management. This study uses a normative legal research method, that is a research examining legal norms prescriptively. The finding of the study indicated that Sad Kertih has a potential to increase environmental awareness among Balinese people and can provide more adaptive solutions to climate change and increasing environmental damage. In conclusion, the application of Balinese local wisdom values ​​through Sad Kertih is very relevant in strengthening environmental control in the modern era, by paying attention to aspects of sustainability and ecosystem balance. Key Word:Sad Kertih, local wisdom, environmental control, sustainability, Bali.